An improved intracellular staining protocol for efficient detection of nuclear proteins in YFP-expressing cells. (December 2011) - Grupillo, Maria; Lakomy, Robert; Geng, Xuehui; Styche, Alexis; Rudert, William A; Trucco, Massimo; Fan, Yong
Intracellular staining is a widely used flow cytometry (FCM)-based technique to detect the expression of cytoslio nucleic antigens. However, intracellular staining of cells expressing cytosolic fluorescent protein (FP) markers was proven to be problematic as significant loss of the FP-signal was routinely observed. Using splenocytes harvested from mice constitutively expressing the enhanced yellow fluorescent proteins (YFP) as a model, we modified the widely used intracellular staining protocol and successfully achieved simultaneous detection of both the nuclar proteins and YFP in T-regulatory cells. The improved protocol can be used to perform antibody-based intracellular characterization of FP-labeled target cells, while maintaining their fluorescent reporter signals for easy tracing and identification.